Research on false information clarification mechanism among government, opinion leaders, and Internet users — Based on differential game theory - Li, Bowen; Li, Hua; Sun, Qiubai; Lv, Rongjian (Frontiers in Psychology, 2022)
This paper regards the government, opinion leaders, and Internet users as constituting a system for correcting false information, and considers the problem of correcting false information that arises in the aftermath of major emergencies. We use optimal control theory and differential game theory to construct differential game models of decentralized decision-making, centralized decision-making, and subsidized decision-making. The solutions to these models and their numerical simulations show that the government, opinion leaders, and Internet users exercise cost-subsidized decision-making instead of decentralized decision-making. The equilibrium strategies, local optimal benefits, and overall optimal benefits of the system achieve Pareto improvement. Given the goal of maximizing the benefits to the system under centralized decision-making, the equilibrium results are Pareto optimal. The research here provides a theoretical basis for dealing with the mechanism of correcting false information arising from major emergencies, and our conclusions provide methodological support for the government to effectively deal with such scenarios.